La diphtongaison ascendante romane et les étapes de l ’évolution du systéme vocalique du latin vulgaire - Pawlik, Janusz (Studia Romanica Posnaniensia, 2003)
The diphthongization in the Romance languages has been a favourite subject o f research for a lot of scholars over the last one hundred and fifty years. Yet, as often is the case with diachronic problems, its origin and circumstances o f creation have divided the opinions o f the historical grammarians. In this essay we will try to consider the diphthongization o f the Vulgar Latin mid Iow vowels, in connection with the overall changes undergone by the Late Latin vocalic system in the stressed position.